Translocação de molibdênio para plântulas de feijoeiro na aplicação de sementes - Carvalho, Ireni Leitzke (2010)
Molybdenum is essential for the bean crop, it influences the metabolism of fixing atmospheric nitrogen, it becomes an indispensable micronutrient for the development of culture. The aim of this study was to evaluate the effect of molybdenum seed treatment on physiological quality of bean seeds and translocation of this chemical element in different stages of seedling development. The treatments were a combination of seed molybdenum, equivalent to 0; 21,5; 43; 64,5 and 86 g.100kg-1. It was used seeds of bean cultivars Expedite and Valente. The physiological quality of seeds was evaluated by germination, first count germination, cold test, accelerated aging, field emergence, emergence rate index, length and dry weight of shoot and root. For the determination of molybdenum translocated, the seeds were sown in trays using washed sand as substrate. At 8, 10, 12 and 14 days after sowing was conducted on the sampling of seedlings. We determined the mass and the molybdenum content of the shoot, by UV-Visible spectrophotometer at 405 nm. The data revealed that there is possibility of applying molybdenum in bean, by seed treatment, in doses of up to 40 g ha-1, without causing damage to the quality and physiological translocated molybdenum content increases linearly with the applied doses.